The Lasting Signatures of Past Landslides on Soil Stripping From Landscapes. Issue 12 (22nd December 2021) - Fan, Linfeng; Lehmann, Peter; Zheng, Chunmiao; Or, Dani
Abstract: Rainfall‐induced shallow landslides scar the Earth surface and deliver sediment pulses into fluvial systems and thus play an important role in landscape evolution. Previous landslide legacy affects local soil depths and soil regeneration rates thus modifying future landslide susceptibility and sediment dynamics. Here, we couple an advanced hydromechanical landslide model with a soil depth regeneration model and quantify landslide legacy effects by placing landslide dynamics in a perspective of landscape soil depth evolution. Results show increased landslide susceptibility near recently failed regions due to alteration of hydrological processes in a thinner soil mantle that imposes constraints on released soil volumes. Landslide recurrence in failed regions levels off when soil depths are gradually restored to steady state pre‐failure values. Cumulative effects of past landslides divert future landslide activity from steep hillslopes to alluvial channels and valley margins thus affecting sediment dynamics and yields. Consideration of landslide legacy improves landslide prediction and quantification of landslide erosion and fluvial sediment yield rates. Key Points: Past landslide signatures are linked mechanistically with future soil failure dynamics and landscape soil depth evolution Soil generation rates and rainfall characteristics jointly determine the persistence of past landslide signatures on future susceptibility Effects of past landslides shift future soil stripping to less steep regions of the landscape and affect fluvial sediment yields